Dads Get Sad Too: Depressive Symptoms and Associated Factors in Expectant First-Time Fathers. (September 2017) - Da Costa, Deborah; Zelkowitz, Phyllis; Dasgupta, Kaberi; Sewitch, Maida; Lowensteyn, Ilka; Cruz, Rani; Hennegan, Kelly; Khalifé, Samir
This cross-sectional study aims to determine the prevalence and determinants of depressive symptoms in first-time expectant fathers during their partner's third trimester of pregnancy. As part of a prospective study examining depressive symptoms in men over the first postnatal year, 622 men (mean age = 34.3 years, ±5.0 years) completed standardized online self-report questionnaires measuring depressed mood, physical activity, sleep quality, social support, marital adjustment, life events, financial stress, and demographics during their partner's third trimester of pregnancy. The Edinburgh Depression Scale was used to assess depressed mood. Partners also completed the Edinburgh Depression Scale in the third trimester. The results revealed that 13.3% of expectant fathers exhibited elevated levels of depressive symptoms during their partner's third trimester of pregnancy. Significant independent factors associated with antenatal depressive symptoms in men were poorer sleep quality, family history of psychological difficulties, lower perceived social support, poorer marital satisfaction, more stressful life events in the preceding 6 months, greater number of financial stressors, and elevated maternal antenatal depressive symptoms. These findings highlight the importance of including fathers in the screening and early prevention efforts targeting depression during the transition to parenthood, which to date have largely focused only on women. Strategies to promote better sleep, manage stress, and mobilize social support may be important areas to address in interventions tailored to new fathers at risk for depression during the transition to parenthood.